Análisis de nueva física del modelo 331 a bajas energías - Martínez, R.; Raba, A. (MOMENTO, 2008)
We discuss the 331 model as an application of a model be- yond the standard model, and we apply the method of least squares used in high energy physics to fit parameters at low energy. We find constraints on some parameters associated to new physics beyond the standard model.